An evaluation of city improvement districts in promoting positive social- spatial structures and management processes: a case study of Hillbrow Ekhaya Improvement District, Johannesburg - Tepkeny, Gloria (University of the Witwatersrand, Johannesburg, 2024)
This study aims to assess the effectiveness of City Improvement Districts (CIDs) in fostering positive social-spatial structures and management processes within urban areas. Specifically, the study focuses on the Hillbrow eKhaya Improvement District in Johannesburg, South Africa, as a case study. The research utilizes a qualitative research design method approach, combining semi-structured questionnaires, in-depth interviews, observation, photography, reconnaissance visits, and qualitative data analysis assessments and transcriptions to provide a comprehensive understanding of the impact of city improvement districts on the local community and urban management. By analysing the Hillbrow eKhaya Improvement District’s initiatives, successes, challenges, and stakeholders' perceptions, the study seeks to contribute valuable insights into the role of city improvement districts in enhancing urban living conditions and social cohesion. Understanding the intricate relationship between physical urban spaces and social interactions is crucial for urban planners, policymakers, and researchers seeking to create vibrant, inclusive, and liveable cities. By evaluating the Hillbrow eKhaya Improvement District, this study intends to provide insights into the potential of improvement districts to promote positive social- spatial structures and effective management processes in urban areas. The findings of this research could inform urban planners, policymakers, and local communities about the benefits and challenges associated with improvement districts, contributing to more sustainable and liveable cities.
A research report submitted in fulfillment of the requirements for the Master degree in Urban Areas, In the Faculty of Engineering and the Built Environment , School of Architecture and Planning, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; City Improvement Districts (CIDs); social-spatial structures; management processes within urban areas; SDG-11: Sustainable cities and communities